2016
DOI: 10.1002/cam4.700
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer screening disparities among immigrant women by world region of origin: a population‐based study in Ontario, Canada

Abstract: Rates of mammography screening for breast cancer are disproportionately low in certain subgroups including low‐income and immigrant women. The purpose of the study was to examine differences in rates of appropriate breast cancer screening (i.e., screening mammography every 2 years) among Ontario immigrant women by world region of origin and explore the association between appropriate breast cancer screening among these women groups and individual and structural factors. A cohort of 183,332 screening‐eligible i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 36 publications
5
78
1
Order By: Relevance
“…Our participation results are consistent with prior Canadian studies that have reported lower breast cancer screening rates among immigrant women and specific immigrant subpopulations 9, 10, 11, 24. Recent data from Ontario, Canada9 demonstrated that among immigrant women, South Asians had the lowest breast screening utilization rate with the age 60‐69 group demonstrating lower screening than those aged 50‐59 years.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our participation results are consistent with prior Canadian studies that have reported lower breast cancer screening rates among immigrant women and specific immigrant subpopulations 9, 10, 11, 24. Recent data from Ontario, Canada9 demonstrated that among immigrant women, South Asians had the lowest breast screening utilization rate with the age 60‐69 group demonstrating lower screening than those aged 50‐59 years.…”
Section: Discussionsupporting
confidence: 92%
“…Geopolitical changes that have taken place over the immigration dates covered by this data file necessitated combining some countries into single groups: countries of the former Union of Socialist Soviet Republics (USSR) were assembled into a “Former USSR State” group; countries of the former Yugoslavia were aggregated into “Former Yugoslavia”; women from the People's Republic of China, Macau, Hong Kong, and Taiwan were combined into a single group labeled “CMHT” in all tables and figures. We created world regions based primarily on groupings of countries used by the World Bank19 and consistent with other recent Canadian studies 9, 20. Immigrant women from countries with <100 total women were pooled into an “Other Immigrant” group within each world region.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations